Diffusion tensor imaging and magnetic resonance spectroscopy in a patient with adult onset tuberous sclerosis complex. (February 2018) - Ishikawa, Hidehiro; Niwa, Atsushi; Asahi, Masaru; Matsuura, Keita; Masuzugawa, Satoshi; Niida, Yo; Maeda, Masayuki; Kondo, Mineo; Tomimoto, Hidekazu
Highlights: We presented an adult TSC case without the classic triad despite a high tuber burden. The patient showed normal MRS findings with the brain lesions. MRS may be useful to evaluate the neurological damage in TSC. Abstract: Tuberous sclerosis complex (TSC) 1 or TSC2 is mutated in most TSC patients. TSC2 mutations are more frequently associated with worse outcomes, earlier age at seizure onset, more severe intellectual disability, and higher tuber load than TSC1 . The degree of white matter involvement is thought to be associated with the severity of neurological impairment. At present, genotype–phenotype correlations and relationship between tuber burden and neurological disability in TSC are debatable. We presented a 43-year-old patient with TSC2 mutation, whose symptom was only incomplete quadrantic visual field deficit in spite of multiple brain tubers. The visual field deficit was thought to be due to a small lesion in the upper medial part of the optic radiation revealed by diffusion tensor imaging. Her brain tubers showed normal findings in magnetic resonance spectroscopy. Our case suggested that neurological and neuropsychiatric manifestations of TSC are affected by the quality rather than number of the lesions. In addition, MRS may be useful to identify the correlation between brain tubers and neurological disability in TSC patients.